Praktik Puja Bakti Pai Wan Fo sebagai Wujud Upaya Kausalya - Nyoto Nyoto (STABN Sriwijaya, 2019)
Mahayana carries out rituals with various purposes, one of the purposes of performing devotional worship is to increase confidence in Buddha Dharma. One way to increase the faith (sradha) of the people is by carrying out the devotional service of the pai wan fo. This worship service is carried out by paying homage to 11,000 Buddhas held for 15 days to welcome the Chinese New Year. The implementation of the worship service was held from 1 to 15 on the lunar calendar or better known as ce it and cap go. This study aims to find out the understanding of the people about upaya kausalya, the purposes and benefits of the devotional service of the pai wan fo, and the constraints on the implementation of pai wan fo. The type of study is descriptive qualitative. So that the data obtained is satisfactory, the authors carry out observations, interviews, and documentation so that the data obtained is accurate. The results of this study are known to the understanding of the people about upaya kausalya, the purposes and benefits of the devotional service of the pai wan fo, and the constraints on the implementation of pai wan fo. From the implementation of this study, it is also known that the implementation of the devotional pai wan fo is to practice Dharma.Aliran Mahayana melaksanakan ritual dengan berbagai tujuan, salah satu adalah meningkatkan keyakinan kepada Buddha Dharma. Salah satu cara agar keyakinan (sradha) umat meningkat adalah dengan melaksanakan puja bakti pai wan fo. Puja bakti ini dilaksanakan dengan memberikan penghormatan kepada 11.000 Buddha yang dilaksanakan selama 15 hari untuk menyambut tahun baru Imlek. Pelaksanaan puja bakti ini dilaksanakan mulai tanggal 1 sampai 15 pada penanggalan lunar atau lebih dikenal dengan istilah ce it sampai cap go. Penelitian yang dilaksanakan untuk mengetahui pemahaman umat tentang upaya kausalya, tujuan dan manfaat puja bakti pai wan fo, dan kendala pelaksanaan puja bakti pai wan fo. Jenis penelitian ini adalah penelitian kualitatif deskriptif. Data diperoleh melalui observasi, wawancara, dan dokumentasi. Hasil penelitian ini adalah diketahui pemahaman umat tentang upaya kausalya, tujuan dan manfaat puja bakti pai wan fo, dan kendala pelaksanaan puja bakti pai wan fo. Dari pelaksanaan penelitian ini diketahui juga bahwa pelaksanaan puja bakti pai wan fo adalah untuk mempraktikkan Dharma.